Demotivating Factors of EFL Learners of Indonesian Undergraduate Students during Pandemic Covid-19: Gender Differences - Imam Santosa; Yasir Riady (Linguists : Journal Of Linguistics and Language Teaching, 2021)
Pandemic covid-19 precedes education to adapt with this disruptive situation. The needs of teaching and learning continuity suggests online learning as one of the solutions along with its challenge. This study aim to investigate whether gender differences influence demotivating factors of EFL Learners of Indonesian Undergraduate Student during pandemic covid-19 situation Surveys design was utilized to verify the hypothesis in this research. On the basis of Kikuchi’s (in press) qualitative study, this study employed 34-item questionnaire that consist of five categories;((a) Course Books, (b) Inadequate School Facilities, (c) Test Scores, (d) Noncommunicative Methods, and (e) Teachers’ Competence and Teaching Styles) to gather quantitative data. Having cluster random sampling as sampling technique, the participants were 368 EFL Learners of Indonesian Undergraduate Student from private universities in Jakarta. The findings of the research revealed that gender did not influence demotivation factors on online learning during pandemic situation. However, the finding indicated the absence of face-to-face teacher in online learning significantly influence demotivating factors on learning English, as non-communicative approach and teacher performance being the most cited factors. Additionally, the result of the study can be the basis of further research on demotivating factors in learning English.